ANALISIS EFISIENSI PEMASARAN BENIH IKAN LELE DUMBO (Clarias gariepinus) MENURUT PENDEKATAN ELASTISITAS PERMINTAAN (STUDI KASUS DI DESA SAGARACIPTA KECAMATAN CIPARAY KABUPATEN BANDUNG) - EVA PRASETIYONO (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2008)
The study was performed to recognize marketing efficiency on cat fish seed sale from seeder to the drain by demand elasticity approach. Beside it, this study also performed to know most efficiency marketing at exist drains. The study located at Sagaracipta Village Ciparay Sub regency Bandung Regency from August 2006 until September 2006. The research method that used was survey method. Survey method is research method that taking the sample from one population and using the questioner as tool to collect main data. There are 3 main features of survey method in this study, that are data collected from respondent (sample of population) that represented all population, data collected by questioner, generally analysis unit is individual. The study result describes that cat fish seed marketing from seeder to the drain in Sagaracipta was not efficient for the drain. It can seen by demand elasticity rate was larger than 1 (e>1). Among 6 drains that exist, there are 4 drains that has more efficient that others, because their Marginal Revenue (MR) rate were large.